Heuristic column generation algorithm for aircraft dynamic scheduling - Fang Jie; Xia Hong-shan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Aircraft dynamic scheduling made a rational organization of surplus aircrafts to generate the optimized aircraft dispatch solution. The approach improved the operation efficiency and aviation enterprise benefits. To describe the complex relationship in aircraft dispatch, according to the characteristics of the airlines operation network, the research constructed an aircraft dynamic time-space network diagram, defined the surplus aircrafts’ routing and constructed corresponding mathematical model. The proposed method found the routings set with heuristic methods in the column generation algorithm sub-problem process. Finally, the given example illustrated the method generate reasonable and practical aircraft solution for airlines in the effective time. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4519